Lack of functional erythropoietin receptors of cancer cell lines - Magdalena Laugsch; Eric Metzen; Tanja Svensson; Reinhard Depping; Wolfgang Jelkmann (2007)
Erythropoietin (Epo) therapy reduces red cell transfusion requirements and improves the quality of life of anemic cancer patients receiving chemotherapy. However, there is concern that Epo may promote tumor growth. We investigated by real-time RT-PCR, immunofluorescence microscopy, Western blotting and cell growth analysis whether human cancer cell lines (SH-SY5Y, MCF7, HepG2, U2-OS, HeLa, HEK293T, RCC4, HCT116, 7860wt and SW480) possess functional Epo receptors (EpoR). We detected EpoR mRNA in all cell lines. Neither hypoxia nor Epo treatment altered the level of EpoR mRNA expression. Four commonly used commercial antibodies proved to be unsuitable for immunoblot procedures because they cross-reacted with several proteins unrelated with EpoR. Depending on the antibody used, EpoR was localized to the plasma membrane, the cytoplasm or the nucleus. Experiments with small interfering RNA showed that EpoR protein was not expressed by the tumor cells except by UT7/Epo leukemia cells, which served as an EpoR positive control line, and by cells transfected with the human EpoR gene. Apart from UT7/Epo, none of the tumor cell lines responded to Epo treatment with phosphorylation of signaling molecules or with cell proliferation.